Kinetics study of membrane anaerobic system (MAS) in palm oil mill effluent (POME) treatment / Abdurrahman Hamid Nour … [et al.] - Hamid Nour, Abdurrahman; Yahya, Asdarina; N. F. S., Amirah; Abdul Rahman, Siti Natrah; Mohammed Manshor, Norasmah; Hassan, Zulkafli (Institute of Research Management and Innovation (IRMI), 2015)
Increasing demands in palm oil industry resulting in the increase in production palm oil. It is then creating a major problem in disposing the waste to be treated in appropriate ways. The governments are forced to look for alternative technology for the palm oil mill effluent (POME) treatment because the demand of oil increases with the awareness on increasing environmental issue. Therefore, a new technology must be found in order to reduce energy consumption, to meet legal requirements on emission and for cost reduction and also increased quality of water treatment. Membrane Anaerobic System (MAS) is a promising alternative way to overcome these issues. In this study, the efficiency of the MAS performance increases to 99.03% in ten days operation. The application ofMonod, Contois and Chen & Hashimoto models were used to analyze the performance of MAS for treating POME. The results from the experiment show the substrate removal model is well fits for estimation of kinetics membrane anaerobic system. Amongst them, the Contois and Monod models predicted the bio-kinetic reactions of the MAS very well with coefficient of determination (R2>97%) values. The MAS bioreactor was created to be an improvement method as well as successful biological treatment since the graph shows linearized which is in good agreement with reported in literature.